Jalan di Depan Tidak Akan Mudah: Metafora dalam Pidato Kemenangan Kamala Harris dan Terjemahannya ke dalam Bahasa Indonesia - Adam, Muhammad (Jurnal Penerjemahan, 2021)
Metaphor in political discourse is common as it helps to shape argumentation. It is also found in Kamala Harris's acceptance speech after she is announced as elected vice president of the United States of America. This study aims to investigate the conceptual metaphor found in Kamala Harris's acceptance speech and to further examine the metaphor mapping scheme of the Indonesian translation results. The data source is Kamala Harris’s Speech text and its Indonesian translation. Conceptual Metaphor Theory (CMT) of Lakoff and Johnson is used as the theoretical framework during metaphor analysis, whereas Mandelbilt (1995) Cognitive Translation Hypothesis is used during the analysis of the metaphor translation process. The result shows that from ten metaphors examined, there are six target domains of conceptual metaphor found; whereas the comparison with the Indonesian translation shows all metaphors fall into Similar Mapping Condition (SMC) with mostly the same wording or lexical expressions. Keywords: Conceptual Metaphor; Political Metaphor; Metaphor Translation; Similar Mapping Condition.